The Effects of Market-based School Reforms on Students with Disabilities - Dudley-Marling, Curt; Baker, Diana (Disability Studies Quarterly, 2012)
Neoliberalism is a theory of political economy which holds that the well-being of individuals is best served by liberating individual entrepreneurial freedom in a framework characterized by strong private property rights, free markets, and free trade. The role of government is limited to keeping people safe and preserving the rules of the market and leaving to the markets services, including education, that it is assumed will be more efficiently delivered by the private sector. Educational policies in the US and in other countries around the world have been strongly influenced by market-based reforms including accountability, high-stakes testing, data-driven decision-making, charter schools, deregulation, and competition among schools. This paper summarizes current theory and research on the effects of market-based schooling practices on students with disabilities. The available evidence indicates that students with disabilities are not well served by market-based reforms and, further, free-market reforms may be fundamentally incompatible with the needs of students with disabilities. Keywords: charter schools; vouchers; educational reform; free-market schooling; school choice; neoliberalism